The Role of Insurance Agents in Enhancing Microinsurance in the VUCA Era at PT. Asuransi BRI Life Medan - Tari Nur Syafni Sinaga; Juliana Nasution (MASI Mandiri Edukasi, 2025)
This study aims to explore the role of insurance agents in increasing microinsurance penetration at PT. Asuransi BRI Life Medan, within the context of the VUCA (Volatility, Uncertainty, Complexity, Ambiguity) era. Although microinsurance, introduced in Indonesia since 2013, has great potential to provide financial protection for low-income communities, public understanding and awareness of the importance of insurance remain relatively low. This condition creates challenges for insurance companies in expanding the reach of microinsurance products. Insurance agents play a crucial role as intermediaries between companies and customers, with responsibilities that include providing education, building trust, and attracting potential customers to microinsurance products. This study employs a qualitative method with a case study approach, conducted through in-depth interviews with insurance agents, marketing managers, and customers of PT. Asuransi BRI Life Medan. The findings reveal that insurance agents utilize various communication channels, both digital and conventional, to introduce and promote microinsurance products to the public. However, agents still face challenges in improving financial literacy and building trust in the benefits of insurance products. These findings underscore the importance of strengthening agents’ capacity and developing innovative communication strategies that are adaptable to the dynamics of the VUCA era, thereby enhancing microinsurance penetration in Indonesia.